AN ANALYSIS OF THE ROLE OF HOPE IN THE QUARTER LIFE CRISIS IN EARLY ADULTHOOD - Adharina, Nurul; Karjuniwati, Karjuniwati; Urrahmah, Asysyifa; Safrilsyah, Safrilsyah; Hidayati, Siti Hajar Sri (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2022)
Early adulthood will experience stress, insecurity, worry, and social pressure regarding life goals, including students, which is called a quarter-life crisis. One factor that affects the quarter-life crisis is hope. This study aims to analyze the relationship of hope with the quarter-life crisis in early adulthood. This study uses a quantitative approach. The measuring instrument in this study uses a quarter-life crisis scale based on Robbins and Wilner's theory and a hope scale based on Snyder's theory. The sample amounted to 330 early adult students. Sampling using non-probability sampling method with purposive sampling technique. The hypothesis of this study was tested using Pearson's product-moment correlation. The study results showed a correlation coefficient (rxy = -0.249) with p = 0.000 (p ˂ 0.05), namely there is a very significant negative relationship between hope and quarter-life crisis in early adulthood, so the hypothesis is accepted. The higher the level of hope in individuals, the lower the level of quarter-life crisis experienced, and vice versa, the lower the hope, the higher the quarter-life crisis experienced by individuals.